Mouse mammary tumor-like virus (MMTV) is present in human breast tissue before development of virally associated breast cancer - Nartey, Teiko (Infect Agent Cancer, 2017)
BACKGROUND: There is substantial evidence that a virus homologous to mouse mammary tumor virus (MMTV) may have a role in human breast cancer. The present study indicates that those who developed breast cancer associated with an MMTV-like virus had this virus in their non-cancerous breast tissues years before the cancer developed. METHODS: Polymerase chain reaction (PCR) techniques and sequencing were used to identify MMTV-like envelope gene sequences (MMTV-like env sequences) in Australian benign breast biopsy specimens from women who several years later developed breast cancer. Murine contamination was excluded by stringent laboratory procedures, and the absence of intracisternal A particle sequences and mitochondrial cyclooxygenase sequences. RESULTS: MMTV-like env sequences (also called HMTV sequences to denote their source) were found in 9 of 25 breast cancer specimens (36%). Among 25 non-cancerous breast biopsies of these same patients taken 1 to 11 years earlier, six contained MMTV-like sequences (24%). Five of the six were among the nine virally-associated breast cancers. In two pairs of specimens, benign and malignant, env sequences were 97% identical. CONCLUSIONS: The identification of MMTV (MMTV-like) sequences in breast tissues prior to the development of MMTV positive breast cancer fulfills a key criterion for a possible causal role for the MMTV-like virus in human breast cancer.